Upaya Orang Tua Buruh Pabrik dalam Membimbing Belajar Anak di Rumah saat Masa Pandemi COVID-19 - Efri Andika Dewi (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
This article aims to examine the efforts of parents of factory workers in guiding children's learning at home during the current Covid 19 pandemic. The emergence of the threat of a pandemic such as Covid 19 which affects all aspects of human life such as health, economy, social, environment, education that has hit and hit the lives of poor parents, schools are closed and causes children to learn from home which must sue parents to accompanying children's learning. The role of parents greatly affects the learning process of children. Support and guidance from parents can motivate children's enthusiasm for learning. In this research using qualitative descriptive research, because the qualitative descriptive method is a problem solving procedure that is observed by describing the condition of the subject and the object of the study. Data collection techniques in this study using observation techniques, interviews, documentation. Parental guidance is very important because it is a process of assistance provided by parents to their children by utilizing existing facilities in order to be able to solve various problems in their child's life.